Motivation of Adidas / Siti Anis Suria Ismail ...[et al.] - Ismail, Siti Anis Suria; Iberahim, Nur Izyana; Ahmad Rosli, Norhamizah (2009)
Our project here is all about “Adidas”. As we all know that Adidas is a product well established in market since 80 years ago. For over these years the Adidas Group has been part of the world of sport on every level, delivering state- of-the-art sports footwear, apparel and accessories. Today, the Adidas Group is a global leader in the sporting goods industry and offers abroad portfolio of products. Products from the Adidas Group are available in virtually every country of the world.